2009
DOI: 10.1007/978-3-642-04180-8_65
|View full text |Cite
|
Sign up to set email alerts
|

Relevance Grounding for Planning in Relational Domains

Abstract: Abstract. Probabilistic relational models are an efficient way to learn and represent the dynamics in realistic environments consisting of many objects. Autonomous intelligent agents that ground this representation for all objects need to plan in exponentially large state spaces and large sets of stochastic actions. A key insight for computational efficiency is that successful planning typically involves only a small subset of relevant objects. In this paper, we introduce a probabilistic model to represent pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Notable examples include reasoning only in terms of the subset of objects that are relevant for current planning purposes (relevance grounding) [12], or using variables to stand in for the objects relevant to the current actions (deictic references) [13].…”
Section: Related Workmentioning
confidence: 99%
“…Notable examples include reasoning only in terms of the subset of objects that are relevant for current planning purposes (relevance grounding) [12], or using variables to stand in for the objects relevant to the current actions (deictic references) [13].…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, feature learning in general is an open and difficult question, which has been considered in many contexts, e.g., [11] and [12]. The possible features include the state label (as discussed previously), as well as any sensory information the agent may receive from the environment.…”
Section: B Feature Selectionmentioning
confidence: 99%
“…Examples include reasoning only in terms of the subset of objects that are relevant for current planning purposes (relevance grounding) [12], or using variables to stand in for the objects relevant to the current actions (deictic references) [28]. This is similar to the way in which pruning is used in search, but we prune based on the expected utility of the action, estimated from its utility in the optimal policies for a set of previous tasks.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to the current paper, however, they assume a given model of the world. Recently, Lang and Toussaint [17] and Joshi et al [12] have shown that successful planning typically involves only a small subset of relevant objects respectively states and how to make use of this fact to speed up symbolic dynamic programming significantly. A principled approach to exploration, however, has not been developed.…”
Section: Related Workmentioning
confidence: 99%